Metode Ijtihad Imam al-Syafi'i dalam Kitab al-Risalah - Djafry, Muhammad Taufan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2016)
Al-RisÄlah is a frst book concerns in ushul fkh. This book is written by Imam al-SyÄfâ€™Ä« rh. and contains explainations on rules of islamic argumentation (istidlÄl) from al-Qurâ€™Än. Al-RisÄlah book has gotten the great credit of moslem schoolars up to nowdays, as it is not only a frst book in ushul fkh but it also contains various knowledges in many felds. Imam SyÄfâ€™Ä« â€˜s view on ijtihÄd and its methodology are explained in this book. Imam SyÄfâ€™Ä«â€™s methods explained in this book are : Making all cases reference to al-Qurâ€™Än, á¸¤ad á¸¤ Ä«á¹¡, IjmÄâ€™, and the á¹£ah á¸¤ Äbahâ€™s sayings and qiyÄs, determining a law by considering a substantial argumet, determining a law by considering the illat and reducing the arguments to the visible matters, and the truth is reverted to Allah. Keyword : IjtihÄd, Uá¹£Å«l al-Fiqh, Imam SyÄfâ€™Ä«